Double Auction Framework to Manage the Secondary Users in Cognitive Radio Networks (Crns) - Elangovan, K.; Subashini, S. (International Journal of Engineering and Technology, 2018)
Cognitive Radio Networks (CRNs) is an emerging concept in wireless access between the users. The CRNs intend towards effective utilization of frequency spectrum when the licensed user is not utilizing the spectrum. The CRNs are vulnerable to security issues like general networks. Security provisioning plays a vital role in CRNs for authorizing the information being shared among the legitimate Primary Users (PUs) and the opportunistic Secondary Users (SUs). This work mainly focuses on the mitigation of selfishness among the unlicensed users during the presence of multiple malicious users. In this work, we consider a beam-forming based Dynamic Spectrum Leasing (DSL) [34] concept to enhance the spectrum utilization for the communication between the primary and secondary users. We propose a Double Auction Framework (DAF) for improving the Selfish SU detection rate during the presence of malicious users to improve the number of opportunistic Users without creating hindrance to the legitimate User. The Simulation results reveal that the DAF-DSL based scheme provides effective spectral gains comparing with the baseline scheme for the secondary users spectrum utilization. Â